2020
DOI: 10.3390/s20041127
|View full text |Cite
|
Sign up to set email alerts
|

Using Hand-Held Chlorophyll Meters and Canopy Reflectance Sensors for Fertilizer Nitrogen Management in Cereals in Small Farms in Developing Countries

Abstract: To produce enough food, smallholder farmers in developing countries apply fertilizer nitrogen (N) to cereals, sometimes even more than the local recommendations. During the last two decades, hand-held chlorophyll meters and canopy reflectance sensors, which can detect the N needs of the crop based on transmission and reflectance properties of leaves through proximal sensing, have been studied as tools for optimizing crop N status in cereals in developing countries. This review aims to describe the outcome of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(21 citation statements)
references
References 119 publications
(185 reference statements)
1
20
0
Order By: Relevance
“…Optimum rates of N are dependent on yearly environmental conditions that are random and cannot be predicted in advance (Raun et al, 2019). Further, the standard general fertilizer N recommendations in a region are always associated with risks of low profits and environmental degradation (Fageria and Baligar, 2005;Ladha et al, 2005;Bijay-Singh, 2018). Ali et al (2017) reported that fertilizer N recovery efficiency in wheat in some parts of Egypt was in the range of 35.6-51.1% by following the standard recommendation.…”
Section: Introductionmentioning
confidence: 99%
“…Optimum rates of N are dependent on yearly environmental conditions that are random and cannot be predicted in advance (Raun et al, 2019). Further, the standard general fertilizer N recommendations in a region are always associated with risks of low profits and environmental degradation (Fageria and Baligar, 2005;Ladha et al, 2005;Bijay-Singh, 2018). Ali et al (2017) reported that fertilizer N recovery efficiency in wheat in some parts of Egypt was in the range of 35.6-51.1% by following the standard recommendation.…”
Section: Introductionmentioning
confidence: 99%
“…[32,33]. Nitrogen fertilizer management using proximal sensors was extensively studied and also practiced in cereals [34,35], vegetables [36] etc. Remote sensing methods using spectral and thermal approaches have potentiality to schedule nitrogen fertilization after rapid identification of nitrogen status in crop canopy across large areas [37].…”
Section: Soil-cum-plant Analysis-based Ssnmmentioning
confidence: 99%
“…@ 30 kg ha -1 as basal, 60 kg ha -1 at CRI stage and Greenseeker guided nitrogen application @ 40 kg ha -1 at 45 days after sowing (DAS) during second irrigation and 10 kg ha -1 at 65 DAS (third irrigation) showed highest benefit cost ratio in wheat production at Kanke, Ranchi, India [66]. Hand-held chlorophyll meters (SPAD meter and atLeaf) and canopy reflectance sensors (GreenSeeker and Crop Circle) can be effectively utilized by small land holding farmers for fertilizer nitrogen management in cereals (rice, wheat and maize) in developing countries [34]. They observed that sensor based nitrogen management had reduced the dose of fertilizer nitrogen application, increased crop productivity and enhanced nitrogen use efficiency.…”
Section: Canopy Reflectance Sensormentioning
confidence: 99%
“…GreenSeeker takes into account the N status and the biomass of the crop to access additional N fertilizer recommendations. It showed a high correlation with in-season N status in wheat (Németh et al, 2007;Bijay and Ali, 2020). However, chlorophyll is the main pigment of plant leaves and responsible for their greenness.…”
Section: Introductionmentioning
confidence: 98%
“…Therefore, N management is crucial as it can volatilize or leach out of the soil and the probability that its requirement is the same in different growing seasons is only about 1% (Zheng et al, 2015). In aditition, the standard N fertilizer references and recommendations cannot include the spatial and in-season variability in soil N supplying capacity during the crop cycle (Gabriel et al, 2017;Bijay and Ali, 2020). Therefore, a split application method is seen as the best way to increase fertilizer use efficiency under potato production.…”
Section: Introductionmentioning
confidence: 99%